How Can We Learn Whether Firm Policies Are Working in Africa? Challenges (and Solutions?) for Experiments and Structural Models - McKenzie, David (2012)
Firm productivity is low in African countries, prompting governments to try a number of active policies to improve it. Yet despite the millions of dollars spent on these policies, we are far from a situation where we know whether many of them are yielding the desired payoffs. This paper establishes some basic facts about the number and heterogeneity of firms in different sub-Saharan African countries and discusses their implications for experimental and structural approaches towards trying to estimate firm policy impacts. It shows that the typical firm program such as a matching grant scheme or business training program involves only 100 to 300 firms, which are often very heterogeneous in terms of employment and sales levels. As a result, standard experimental designs will lack any power to detect reasonable sized treatment impacts, while structural models which assume common production technologies and few missing markets will be ill-suited to capture the key constraints firms face. Nevertheless, the author suggests a way forward which involves focusing on a more homogeneous sub-sample of firms and collecting a lot more data on them than is typically collected.